Patent Selections: - Bentham Science Publishers (Recent Patents on Food, Nutrition & Agriculture, 2012)
The patents annotated in this section have been selected from various patent databases. These recent patents are relevant to the articles published in this journal issue, categorized by food additives, micro & macro-molecular food supplements, edible alternatives, food technology, nutraceuticals, healthy diet, nutritional value, calorie intake, malnutrition & related diseases, plant derivatives, agricultural technology and products, crop improvement and safety issues related to food, nutrition & agriculture....